2013
DOI: 10.1021/sb400147n
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Engineering of the Synthetic Pathway for Biodegradation of a Toxic Persistent Pollutant

Abstract: Anthropogenic halogenated compounds were unknown to nature until the industrial revolution, and microorganisms have not had sufficient time to evolve enzymes for their degradation. The lack of efficient enzymes and natural pathways can be addressed through a combination of protein and metabolic engineering. We have assembled a synthetic route for conversion of the highly toxic and recalcitrant 1,2,3-trichloropropane to glycerol in Escherichia coli, and used it for a systematic study of pathway bottlenecks. Opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 35 publications
(58 reference statements)
1
60
0
Order By: Relevance
“…Insertion of oxygen preferentially occurs on the terminal carbon, yielding chlorinated carbonyl compounds that undergo an elimination reaction to produce the very toxic compound 2-chloroacrolein (14). Genetic engineering may offer a strategy for producing a strain for the aerobic degradation of TCP (15)(16)(17). Theoretical calculations have indicated that a number of transformations, including reductive dechlorination, reductive ␤-elimination, dehydrochlorination, and nucleophilic substitution by OH Ϫ , are thermodynamically favorable (18).…”
mentioning
confidence: 99%
“…Insertion of oxygen preferentially occurs on the terminal carbon, yielding chlorinated carbonyl compounds that undergo an elimination reaction to produce the very toxic compound 2-chloroacrolein (14). Genetic engineering may offer a strategy for producing a strain for the aerobic degradation of TCP (15)(16)(17). Theoretical calculations have indicated that a number of transformations, including reductive dechlorination, reductive ␤-elimination, dehydrochlorination, and nucleophilic substitution by OH Ϫ , are thermodynamically favorable (18).…”
mentioning
confidence: 99%
“…One of the proposed strategies for decontamination of water from TCP is bioremediation. Haloalkane dehalogenase was engineered for enhanced efficiency of the degradation of TCP [35] and coupled with another two enzymes haloalcohol dehalogenase and epoxide hydrolase to convert TCP via several intermediates to glycerol and chloride ions [24][25][26]36]. The bacteria containing these enzymes are tested to be used for bioremediation purposes [35,37].…”
Section: Using the Microfluidic Sers Detector With Sk307 For Environmmentioning
confidence: 99%
“…With SK307, we developed a simple and versatile optofluidic SERS-based diagnostic and analytical system which provides fast and reliable quantitative measurement of organic chemicals, such as halogenated hydrocarbons. Specifically we were able to detect a toxic environmental pollutant 1,2,3-trichloropropane (TCP) [24][25][26] in water at submillimolar concentrations. We also tested our optofluidic SERS system with other analytes such 2,3-dichloropropan-1-ol (DCP) and trichloromethane (CHCl3).…”
Section: Introductionmentioning
confidence: 99%
“…Biocatalytic cascades are particularly successful because enzymes can be selected to have similar temperature and pH requirements in aqueous buffers. [5] Investigating complex systems can have enormous potential, but as molecular complexity increases, chemical transformations increase in parallel. [4] Kurumbang, et al synthetically derived a method for decreasing halogenated hydrocarbons that threaten human health and the environment using a five-step pathway and three enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Kurumbang, et al synthetically derived a method for decreasing halogenated hydrocarbons that threaten human health and the environment using a five-step pathway and three enzymes. [5] Investigating complex systems can have enormous potential, but as molecular complexity increases, chemical transformations increase in parallel. Bimodal catalysts take advantage of two worlds of materials.…”
Section: Introductionmentioning
confidence: 99%